2014
DOI: 10.1002/rcr2.84
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pleural mesothelioma presenting as a spontaneous pneumothorax

Abstract: Malignant pleural mesothelioma (MPM) is thought to arise from the mesothelial cells that line the pleural cavities. Most patients initially experience the insidious onset of chest pain or shortness of breath and have a history of asbestos exposure. MPM rarely presents as spontaneous pneumothorax. We report two male patients who presented with a spontaneous hydropneumothorax. One was exposed to asbestos and the other was not. Computed tomography showed tiny nodules with pleural thickness. They both underwent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…As stated by Prasad and colleagues in 2013 [ 32 ], until then, in the literature, less than 35 cases of MPM presenting as spontaneous pneumothorax have been collected. Mitsui et al [ 33 ], reviewing Japanese literature, reported a total of 16 MPM patients with spontaneous pneumothorax: 81% were male, and concurrent pleural effusion was present in 56% of cases. Recently, Sattar and colleagues [ 34 ] focused exclusively on patients with MPM presenting as hydropneumothorax.…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…As stated by Prasad and colleagues in 2013 [ 32 ], until then, in the literature, less than 35 cases of MPM presenting as spontaneous pneumothorax have been collected. Mitsui et al [ 33 ], reviewing Japanese literature, reported a total of 16 MPM patients with spontaneous pneumothorax: 81% were male, and concurrent pleural effusion was present in 56% of cases. Recently, Sattar and colleagues [ 34 ] focused exclusively on patients with MPM presenting as hydropneumothorax.…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…Not only did the patient present with non-specific symptoms, but the initial CT scan did not show any pleural abnormality, and pleural fluid analysis was negative for malignant cells. Few case reports have noted recurrent hydropneumothorax as the only presenting feature of mesothelioma [4] , [5] , [6] , [7] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Average age: 67 years old; 100% male predominance; marked tobacco history; ubiquitous right thorax involvement; and epithelioid tissue subtype was ubiquitously described [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Case Report Age Sex Environmental Exposure Tobacco Exposure Chief Complaint Chest Roentograph Cytology Biopsy Subtype of MPM DeLapp et al [ 12 ] 67 M Asbestos Yes Cough, Dyspnea Right hydropneumothorax Negative VATS- Biopsy + Epithelioid Fayed et al [ 11 ] 69 M Asbestos No Cough, Dyspnea Bilateral hydropneumothorax Negative VATS- Biopsy + Not clarified Saleh et al [ 10 ] 71 M Asbestos Yes Chest Pain, Dyspnea Right hydropneumothorax Negative VATS- Biopsy + Epithelioid Saleh et al [ 10 ] 70 M Unclear Yes Chest Pain, Dyspnea Right hydropneumothorax Not Declared Open Thoracotom Epithelioid Wu et al [ 9 <...>…”
Section: Case Presentationmentioning
confidence: 99%
“…Large scale and minimally symptomatic progressive hydro-pneumothorax carries a wide range of differentials, and malignant mesothelioma is an obscure diagnosis which requires a high index of suspicion and extensive occupational history investigation on the part of the clinician. Spontaneous hydro-pneumothorax is a rare presentation of MPM, with a literature review of PubMed (search criteria: Mesothelioma, pneumothorax, hydro-pneumothorax) revealing 9 total case reports [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. We present a case of a MPM without documented asbestos exposure, presenting as recurrent right-sided hydro-pneumothorax.…”
Section: Introductionmentioning
confidence: 99%